Hak Pengemudi Bus Perusahaan Angkutan Jalan Perum Damri Surabaya Terkait Jam Kerja - Doel Susanto (Darma Cendika Catholic University, 2018)
The working time of the bus driver as implied by Article 90 paragraph (4) of Law Number 22 of 2009 on Road Traffic and Transportation, is not in sync with Law Number 13 of 2003 concerning Labor because based on the principle of lex specialis derogat legi generali, the status of Perum Damri Surabaya as a type of work engaged in certain business sectors or occupations and the type and nature of work carried out continuously. This affects the wages earned by bus drivers in the form of basic wages and overtime pay. The government has not specifically regulated the provisions of overtime drivers' wages, so that by Law Number 13 of 2003 concerning Manpower and Article 12 of the Decree of the Minister of Manpower and Transmigration of the Republic of Indonesia Number KEP. 102 / MEN / VI / 2004 concerning Overtime and Overtime Working Time shall be submitted to Perum Damri Surabaya to regulate overtime pay. This has potential violations in the payment of overtime wages, so a regulation that specifically regulates the bus driver's overtime wages.